2001
DOI: 10.1037/0022-0167.48.4.384
|View full text |Cite
|
Sign up to set email alerts
|

A close look at conflictual supervisory relationships: The trainee's perspective.

Abstract: In a qualitative study of negative supervision, 13 master's and doctoral trainees were interviewed about a supervision experience that had a detrimental effect on their training. Many supervisors were described as not being invested in the relationship and as being unwilling to own their role in conflicts. Many trainees described being overworked without proper supervision, some felt expected to support their supervisors, and many underwent extreme stress and self-doubt. Most participants reported ongoing powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
248
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(270 citation statements)
references
References 25 publications
20
248
1
Order By: Relevance
“…Even supervisors find it difficult to give feedback to supervisees about the supervisory relationship (Hoffman et al, 2005), so it is not surprising that interns, who are one down in the power relationship, felt it too risky to address their concerns. Nelson and Friedlander (2001) similarly found that problems in poor supervisory relationships went unresolved.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Even supervisors find it difficult to give feedback to supervisees about the supervisory relationship (Hoffman et al, 2005), so it is not surprising that interns, who are one down in the power relationship, felt it too risky to address their concerns. Nelson and Friedlander (2001) similarly found that problems in poor supervisory relationships went unresolved.…”
mentioning
confidence: 81%
“…Advanced trainees may be more susceptible to role conflict than novice trainees because they expect, and may have already experienced, collegial and collaborative supervisory relationships Nelson & Friedlander, 2001;Olk & Friedlander, 1992). As evidenced by the low scores on the SSI, however, interns in problematic relationships did not report collegiality from their supervisors and may also have felt that their supervisors did not acknowledge their clinical experience.…”
mentioning
confidence: 99%
“…Some of the stressors identified in the survey cannot be thought of as essential or necessary aspects of training -for instance, poor supervision of client work (see also Nelson & Friedlander, 2001), and (something that affects clinical far less than counselling psychology trainees in the UK) financial costs, such as fees, loss of earnings while training, childcare, personal therapy and extra supervision (see also Jensen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Social support has been shown to reduce a number of negative outcomes including increases in cardiovascular symptoms and negative affect (Buunk & Verhoeven, 1991;Evans & Steptoe, 2001;Halbesleben, 2006;Peeters et al, 1995). In a qualitative study, Nelson and Friedlander (2001) found that students experiencing conflict with their supervisors often turned to peers for support. Peeters and colleagues (1995) used a longitudinal design to measure female secretaries' stressful events, perceived social support, and negative affect over a one-week period and found within-and between-person buffering effects of task related social support.…”
Section: The Moderating Role Of Social Support In the Workplacementioning
confidence: 99%